Surfactant Protein A Serum Level in Cement Worker - Gunawan Gunawan; Sita Laksmi Andarini; Muhammad Ilyas; Arif Santoso; Ahmad Hudoyo; Irawaty Djaharudin; Harun Iskandar; Nur Ahmad Tabri (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2022)
Background: Pneumoconiosis occurs almost in entire worldwide. Pneumoconiosis had threatened cement workers. Serologic abnormalities had found in pneumoconiosis. Surfactant Protein A (SP-A) levels increased in silica-exposed workers. Surfactant Protein A (SP-A) may be a helpful biomarker for the early diagnosis of pneumoconiosis, but it has not yet been studied in Indonesia.Methods: The design of this study was observational with cross-sectional. A sampling of cement-exposed workers was done by consecutive sampling. The subjects were 88, approach population of 67 cement exposed workers from September 2017 – March 2018 and 17 healthy people as control. The serum level of SP-A was measured by the ELISA method. Cement exposed workers is a worker in the production area and workers in the quarry area.Results: The total number of research subjects met the criteria was 67, and the control subjects were 21. The mean serum SP-A level in the study subject group or the exposed group was 6.02 ng/ml, and the mean SP-A level in the control group was 4.50 ng/ml. The difference in SP-A levels between the exposed and control groups was different but not significant, with value of P=0.084.Conclusion: SP-A levels in the exposed and control groups were different but not statistically significant.